Breathing freely is possible! How to help patients with bronchial asthma and polyposis rhinosinusitis? - Editorial Board ("Consilium Medicum" Publishing house, 2021)
On June 2325, under the auspices of the Year of Science and Technology in Russia, the 17th International Interdisciplinary Congress of Allergology and Rhinosinusitis was held in Moscow. The 17th International Interdisciplinary Congress of Allergology and Immunology, where the results of current research, approaches to therapy and prevention of diseases based on modern clinical guidelines were presented. The event included a symposium "Breathe freely it is possible! How to help patients with bronchial asthma and polyposis rhinosinusitis?" with the participation of leading Russian specialists.